2013
DOI: 10.1021/mp4001102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of P-glycoprotein in Human Brain Capillaries

Abstract: Considering its role as a major blood-brain barrier gatekeeper, the dynamic regulation of the efflux transporter P-glycoprotein is of considerable functional relevance. In particular, disease-associated alterations in transport function might affect central nervous system drug efficacy. Thus, targeting regulatory signaling cascades might render a basis for novel therapeutic approaches. Using capillaries freshly prepared from patient tissue resected during epilepsy surgery, we demonstrate dynamic regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 42 publications
(95 reference statements)
2
51
2
1
Order By: Relevance
“…2B). The concentration of glutamate for this and further experiments was chosen based on previous experimental and clinical studies demonstrating a respective extracellular concentration of glutamate during epileptic seizures and confirming an impact of this concentration on P-glycoprotein expression and function (Thomas et al, 2003(Thomas et al, , 2004(Thomas et al, , 2005Bauer et al, 2008b;Avemary et al, 2013). As expected, MK-571 exerted a relevant inhibitory effect on MRP2-mediated luminal Texas Red accumulation (Fig.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…2B). The concentration of glutamate for this and further experiments was chosen based on previous experimental and clinical studies demonstrating a respective extracellular concentration of glutamate during epileptic seizures and confirming an impact of this concentration on P-glycoprotein expression and function (Thomas et al, 2003(Thomas et al, , 2004(Thomas et al, , 2005Bauer et al, 2008b;Avemary et al, 2013). As expected, MK-571 exerted a relevant inhibitory effect on MRP2-mediated luminal Texas Red accumulation (Fig.…”
Section: Resultssupporting
confidence: 56%
“…Previous studies have reported a glutamate-induced signaling at ASPET Journals on May 11, 2018 jpet.aspetjournals.org via NMDA receptors to activate a cascade of intracellular events that culminates with P-glycoprotein upregulation (Bauer et al, 2008b;Avemary et al, 2013). Thus, we hypothesized that the upregulation of MRP2 might also be related to signaling via NMDA receptors.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations